Prospective Short-term MRI controlled investigation of the healing properties of the Meniscus. Issue 4 (27th April 2017) - Willinger, Lukas; Förschner, Felix; Imhoff, Andreas; Herbst, Elmar
Aims and Objectives: The purpose of the study was to prospectively investigate signal alterations in short-term follow-up after acute meniscus repair on specific magnetic resonance imaging (MRI) scan sequences. It was hypothesized that 1) there are different meniscus healing properties depending on lesion configuration and size, and 2) the tear zone has an influence on the healing properties of the meniscus. Materials and Methods: We conducted this prospective short-term clinical and radiological study to investigate the healing properties of acute meniscus tears. Inclusion criteria were patients (age 18-45 years) with traumatic meniscus lesion, subsequent arthroscopic meniscus repair within 6 weeks and preoperative MRI. Exclusion criteria were age < 18 or >45 years, arthrosis > grade III and multiligamentous knee injuries. Clinical examination and outcome scores (IKDC, KOOS, Lysholm Score) were surveyed preoperatively and 12 weeks after surgery. Meniscus tears were classified according to the ISAKOS meniscus classification system on MRI scans. Radiological assessment using a 3T-MRI was performed preoperatively and 2, 4, 6 and 12 weeks after operation. Meniscus healing were classified according to Henning's criteria in A) healed, B) partially healed (> 50%) and C) not healed. Data were analyzed using SPSS statistics software version 21 (IBM, New York, USA). Statistical significance was set at a p value of < 0.05. Results: These are preliminary results of 14 patients (13 m, 1w) with a total of 16 meniscus tears. According to the ISAKOS meniscus classification system 9 medial and 7 lateral meniscus tears were included and average tear length was 21.5 mm (6 - 40 mm). 12 tears were located in the rim zone 1 and 4 tears were more medially in zone 2. In 8 (57%) patients an additional anterior cruciate ligament (ACL) reconstruction was performed. Six weeks postoperatively 8 menisci (50%) were deemed healed, 6 menisci (37%) partially healed whereas 2 menisci were not healed (13%). After 12 weeks 9 menisci (56%) were considered healed, 4 menisci (25%) partially healed and 3 menisci (19%) showed intrameniscal joint fluid in more than 50% of meniscus thickness. Two bucket handle tears of the medial meniscus and one radial tear of the lateral meniscus, all located in the red-red zone sized 35 mm, 25 mm and 12 mm, were not healed after 12 weeks. Clinical scores improved significantly 12 weeks after surgery: IKDC Score (preOP: 46.7, postOP: 67.8), KOOS (preOP: 49.7, postOP: 79.1) and Lysholm Score (preOP: 49.5, postOP: 77.7) (p < 0.05). Conclusion: Clinical and radiological follow-up showed good short-term results after meniscus repair. MRI revealed signal alteration in all menisci after 12 weeks, in most instances considered as scar tissue without intrameniscal joint fluid. In this cohohrt tear size and location was not correlated with non-healing. Arthroscopic meniscus repair achieves a high healing response of the meniscus and good clinical outcomes.